2019
DOI: 10.3390/ma12223705
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Properties of Alkali-Phenolic Binder in Terms of Selection of Molding Sand for Steel Castings

Abstract: This article presents the results of experiments related to the process of replacement of the currently used furfuryl resin molding sand technology with a new alkali-phenolic technology. The new binder is characterized by a set of technological advantages and is considered more ecological compared to the furfuryl resin. However, the molding sand produced on the basis of the alkali-phenolic resin features lower strength compared to the sands containing furfuryl resin. This article presents a comparative study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Then the sample is removed from the mold. The samples were then stored for 24 h at room temperature for maximum strength (Łucarz et al 2019;Ghosh 2020).…”
Section: Preparation and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the sample is removed from the mold. The samples were then stored for 24 h at room temperature for maximum strength (Łucarz et al 2019;Ghosh 2020).…”
Section: Preparation and Methodsmentioning
confidence: 99%
“…The green sand mold is the type of mold that is most widely used in the world because of the availability of raw materials for sand and bentonite, easy recycling, established processing technology, and the lowest total cost per kg of mold compared to other types of molds. However, limitations such as dimensional accuracy, surface finish, ability to make large products, and the soundness of castings, in this case, are overcome by using a chemical bonded sand process instead of a green sand mold with clay or bentonite binder (Brown 2000;Łucarz et al 2019; Reddy 2019; Khandelwal and Ravi 2020;Ghosh 2020;Brown 1999). Its caused by the mechanical properties of chemically bonded sand, such as the compressive strength values are up to 38 kg/cm 2 , which is higher than the green sand strength values are just about 1.5 kg/cm 2 (Brown 2000;1999).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, alkali-phenolic resin is replacing furan resin in cast steel foundries for ecological and economic reasons [ 8 ]. The results of studies on the use of the Alphaset alkali-phenolic resins from different manufacturers and using different grain matrices were presented by the authors in [ 9 ]. They concluded that, based on comparative studies, a suitable alkali-phenolic resin could be identified (adopting the criterion of the highest moulding sand strength) that is predisposed as a substitute for furan resin.…”
Section: Introductionmentioning
confidence: 99%
“…Achieving high-quality, dimensionally accurate castings that exhibit smooth surfaces and are devoid of pinhole defects necessitates the use of suitable binder system enabling: (i) a high level of structural integrity of moulds and cores through adequate strength and thermo-mechanical stability of composite dimensions [8,9] upon exposure to high-temperature and dynamic and static pressures [2] exerted by molten metal in mould cavities, (ii) the fast-speed and low-cost fabrication of moulds and cores, (iii) minimal gaseous byproduct formation and kinetics during the binder and residual moisture decomposition [9][10][11][12][13], (iv) adequate composite permeability enabling the rapid evacuation of gaseous byproducts evolving in mould cavity upon exposure to liquid metal at the initial stages of its flow and solidification, whilst simultaneously preventing molten metal ingress into inherently porous composite structures, (v) low fracture energy of composites (moulding sand), essential for good mould/core system 'collapsibility' (shakeout) during casting removal and cleaning [2] and (vi) the absence of sintered sand residues adhering to the surface of casting. Geometrical aspects of particulate-filled composites morphology controlling their interior 3-D structure and functional properties: engineering composites in comparison with permeable moulding sand composites: (a) typical engineering composite comprising: (i) particulate filler compacted to achieve the maximum achievable packing density of reinforcing material (74%) according to face-centred cubic (FCC) packing (or hexagonal closest packing; HCP) manner [3] and (ii) polymeric matrix material (binder: 26%) completely filling all porous cavities between compacted particles; (b) FCC-packed permeable composite material (74% filler) with individual filler particles coated by very thin, continuous binder film, as typically observed in moulding sands bonded with liquid organic [1,2,4,5] or inorganic binders [6,7]; (c) inter-particle pendular bridges connecting individual filler particles (an example of an FCC-packed permeable composite filled with uniform diameter spherical particles); this is an optimum structure of moulding sand composite facilitating maximisation of composite strength whilst minimising the binder contents; (d) inter-particle pendular bridges between filler particles: a permeable composite with cubic lattice compacting, achieving packing density of 52.36% [3].…”
Section: Introductionmentioning
confidence: 99%
“…Achieving high-quality, dimensionally accurate castings that exhibit smooth surfaces and are devoid of pinhole defects necessitates the use of suitable binder system enabling: (i) a high level of structural integrity of moulds and cores through adequate strength and thermo-mechanical stability of composite dimensions [8,9] upon exposure to hightemperature and dynamic and static pressures [2] exerted by molten metal in mould cavities, (ii) the fast-speed and low-cost fabrication of moulds and cores, (iii) minimal gaseous by-product formation and kinetics during the binder and residual moisture decomposition [9][10][11][12][13], (iv) adequate composite permeability enabling the rapid evacuation of gaseous by-products evolving in mould cavity upon exposure to liquid metal at the initial stages of its flow and solidification, whilst simultaneously preventing molten metal ingress into inherently porous composite structures, (v) low fracture energy of composites (moulding sand), essential for good mould/core system 'collapsibility' (shakeout) during casting removal and cleaning [2] and (vi) the absence of sintered sand residues adhering to the surface of casting.…”
Section: Introductionmentioning
confidence: 99%